Exploring the experiences of traditional practitioners while managing hypertension in Rwanda - Liberee Kubwimana; Marie Immaculee Dusingize; Delphine Mizero; Gislaine Mutatsineza; Fred Nkurunziza; Peace Ingabire; Arsene Hobabagabo; Rex Wong (BMC, 2024)
Abstract Background Hypertension (HTN) is a major global health concern, affecting approximately 1.28 billion adults worldwide. In Rwanda, hypertension contribute to 2.81 of the disability adjusted life years (DALYs) and 1.87% of hypertensive heart disease mortality. Traditional medicine remains popular in Africa with some herbal remedies which have shown antihypertensive properties. However, no study was done to explore traditional Practitioners' approach to hypertension in Rwanda. Objective To explore the experience of traditional Practitioners while managing hypertension in Rwanda. Methodology This qualitative study utilized an ethnographic approach to explore the experience of traditional Practitioners (TPs) while managing HTN in Rwanda. Semi- structure interviews were conducted with 20 traditional Practitioners from three districts known for their popular use of traditional medicine in Rwanda. Participants were purposively selected, and interviews were guided by a pretested semi-structured interview guide in local language. Thematic analysis was used to generate the key themes. Results Three main themes emerged from analysis: first, traditional medicine is often undervalued by modern medical providers, resulting in limited collaboration and communication between traditional Practitioners and modern medical providers. Despite this, TPs are trusted by the community, often receiving referrals from patients dissatisfied with modern treatment. Second, TPs face challenges in diagnosing HTN due to lack of diagnostic tools, often relying on their observation, patients' description of symptoms and patient's response to treatment. TPs expressed desire for collaboration with modern medicine and access to diagnostic tools. Third, lack of legal framework and standardized practices for traditional medicine remains a challenge. Conclusion The study highlights the need to promote collaboration between traditional and modern medicine in Rwanda. To enhance HTN management, we recommend training of traditional Practitioners, setting standardized practice and legal framework to guide traditional Practitioners in Rwanda as well as improving their access to HTN diagnostic tools.